Педагогічні умови формування готовності майбутніх офіцерів-правоохоронців до виконання завдань за призначенням у системі тактико-спеціальної підготовки - Ковальов, І. М.; Kovalov, I. M.; ORCID: http://orcid.org/0000-0003-0151-388X; Гоговський, Є. В.; Hohovskyi, Ye. V.; Пашуба, А. С.; Pashuba, A. S.; Самойленко, В. М.; Samoilenko, V. M.; Толокнєєв, В. О.; Toloknieiev, V. O. (Педагогіка формування творчої особистості у вищій і загальноосвітній школах. - 2021. - № 76, т. 1. - С. 166-173, 2021)
Розроблено педагогічні умови формування готовності майбутніх офіцерів-правоохоронців до виконання завдань за призначенням у системі тактико-спеціальної підготовки з використанням засобів фізичної та спеціальної фізичної підготовки. Наголошено, що упровадження засобів спеціальної фізичної підготовки, сучасного наукового інструментарію, в основну частину практичних занять із тактико-спеціальної підготовки забезпечить більш стійке, технічно правильне і збалансоване формування необхідних прикладних рухових навичок у майбутніх офіцерів, які забезпечують формування в них професійних компетентностей, необхідних для виконання завдань за призначенням у різних умовах службово-оперативної / бойової діяльності.

Understanding the changes taking place against the background of the armed conflict in eastern Ukraine, the current state of crime is the basis for choosing effective ways to build a law enforcement system in the interests of public safety, so the priority and priority tasks of law enforcement officials (Institutions of the Security and Defense Sector of Ukraine) is the training of a highly competent law enforcement officer, the development of modern educational programs, the creation of a network of educational institutions with specific training conditions (higher military educational institutions) relevant Institutions of the Security and Defense Sector of Ukraine and building profile scientific potential. The above gives grounds to assert that it is possible to train a modern law enforcement officer in an environment in which appropriate pedagogical conditions will be created to improve technologies and teaching methods, which will contribute to the effective formation of professional competencies of such specialists. The main purpose of the study is to develop pedagogical conditions for the formation of readiness of future law enforcement officers to perform assigned tasks in the System of Tactical Special Training using the means of Physical and Special Physical Training (Technical means of Training). During the theoretical study we used the following methods: idealization, formalization, axiomatic, historical and logical, ascent from the specific, the experience of training representatives of the security and defense sector of Ukraine to perform assigned tasks, combat experience and operational experience. As the basic means of physical training we have chosen complexes of physical exercises which provide preparation of an organism of future officers to performance of motor tasks (working out of educational questions of the basic part) during practical classes on Tactical and Special Training. As a means of Special Physical training, we have selected some elements of the technique of applying Physical measures (strength), special running exercises and exercises on the obstacle course, and so on. An important tool is the use of «Katsumoto» rapid computer analysis of biomechanical movements during practical training in Tactical and Special training. In addition, during practical classes on Tactical and Special training it is planned to use a methodological approach adapted to the needs of police training to assess the video material used in the training of combatants (Martial Arts athletes). The choice of functional and technical means of training of the above is due to the need for effective formation of professional competencies of future law enforcement officers, which are necessary for them to perform the tasks assigned to them in primary officer positions. We are expected to implement in the educational process (System of Tactical Special Training) future law enforcement officers of the pedagogical conditions developed by us will ensure the formation of their integrated (common) and special (professional, subject) competencies that will promote high-quality, reliable and effective performance of their assigned tasks in different conditions of service and operational (combat) activities.

Разработаны педагогические условия формирования готовности будущих офицеров правоохранителей к выполнению задач по назначению в системе тактико-специальной подготовки с использованием средств физической и специальной физической подготовки. Отмечено, что внедрение средств специальной физической подготовки, современного научного инструментария, в основную часть практических занятий по тактико-специальной подготовке обеспечит более устойчивое, технически правильное и сбалансированное формирование необходимых прикладных двигательных навыков у будущих офицеров, обеспечивающих формирование у них профессиональных компетентностей. выполнение задач по назначению в разных условиях служебно-оперативной/боевой деятельности.
Pedagogical conditions for the formation of readiness of future law enforcement officers to perform assigned tasks in the System of Tactics of Special Training
Ковальов, І. М. Педагогічні умови формування готовності майбутніх офіцерів-правоохоронців до виконання завдань за призначенням у системі тактико-спеціальної підготовки / Ковальов І. М., Гоговський Є. В., Пашуба А. С. та ін. // Педагогіка формування творчої особистості у вищій і загальноосвітній школах. - 2021. - № 76, т. 1. - С. 166-173.- DOI: https://doi.org/10.32840/1992-5786.2021.76-1.32.
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; Фізична культура. Спорт. Physical Education. Sport. Физическая культура. Спорт; Україна. Ukraine. Украина; професійна освіта; professional education; профессиональное образование; майбутні офіцери-правоохоронці; future law enforcement officers; будущие офицеры-правоохранители; педагогічні умови; pedagogical conditions; педагогические условия; тактико-спеціальна підготовка; tactical special training; тактико-специальная подготовка; професійна компетентність; professional competence; профессиональная компетентность; спеціальна фізична підготовка; special physical training; специальная физическая подготовка; заходи поліцейського примусу